Specific macrophage populations promote both cardiac scar deposition and subsequent resolution in adult zebrafish. Issue 7 (16th August 2019) - Bevan, Laura; Lim, Zhi Wei; Venkatesh, Byrappa; Riley, Paul R; Martin, Paul; Richardson, Rebecca J
Abstract: Aims: A robust inflammatory response to tissue injury is a necessary part of the repair process but the deposition of scar tissue is a direct downstream consequence of this response in many tissues including the heart. Adult zebrafish not only possess the capacity to regenerate lost cardiomyocytes but also to remodel and resolve an extracellular scar within tissues such as the heart, but this scar resolution process remains poorly understood. This study aims to characterize the scarring and inflammatory responses to cardiac damage in adult zebrafish in full and investigate the role of different inflammatory subsets specifically in scarring and scar removal. Methods and results: Using stable transgenic lines, whole organ imaging and genetic and pharmacological interventions, we demonstrate that multiple inflammatory cell lineages respond to cardiac injury in adult zebrafish. In particular, macrophage subsets ( tnfα+ and tnfα − ) play prominent roles with manipulation of different phenotypes suggesting that pro-inflammatory ( tnfα+ ) macrophages promote scar deposition following cardiac injury whereas tnfα − macrophages facilitate scar removal during regeneration. Detailed analysis of these specific macrophage subsets reveals crucial roles for Csf1ra in promoting pro-inflammatory macrophage-mediated scar deposition. Additionally, the multifunctional cytokine Osteopontin (Opn) ( spp1 ) is important for initial scar deposition but also for resolution of the inflammatory response and in late-stage ventricular collagen remodelling. Conclusions: This study demonstrates the importance of a correctly balanced inflammatory response to facilitate scar deposition during repair but also to allow subsequent scar resolution, and full cardiac regeneration, to occur. We have identified Opn as having both pro-fibrotic but also potentially pro-regenerative roles in the adult zebrafish heart, driving Collagen deposition but also controlling inflammatory cell resolution. Graphical Abstract: